Dynamic Analysis of Instability in Three-Wheeler Automobile Vehicle - , Chukwutoo C. Ihueze; , Paschal S. Ebisike (Archives of Current Research International, 2018)
At pre-design stage of three wheeler automobile vehicle, engineers are posed to use simple models to show the fundamental and functional characterizations of the vehicle. Wobbling instability is consider as one of the major problems of a three wheeled automobile vehicle, and are of great interest to industry and academia. This study outlines the effect of applying camber angles on the handling and lateral stability of a three wheeled automobile vehicle and the use of a rigid body model with two variables, the sprung mass and un-sprung mass. This study investigates the effect of applying camber angles on the vehicle handling, lateral stability, ride comfort and skid of a three-wheeled automobile vehicle. Due to the unbalance nature of the vehicle, controlling the instability especially during turning, cornering and harsh maneuver is very challenging. Hence the stability is ensured by the introduction of an active camber system to the vehicle suspension system. Which are determined by modeling the (quarter car model) vehicle movement using harmonic and transient responses over isolated road bump model and the forces generated on each part of the suspension system are analyzed.